OPTIMASI PENGGUNAAN PEMANIS STEVIA DAN PENGARUHNYA TERHADAP KUALITAS SENSORIS DAN STABILITAS WARNA SIRUP BUNGA TELANG (CLITORIA TERNATEA L.) - Marlina, Lusi; Pujiastuti, Sari Dewi (Jurnal TEDC, 2024)
This study aims to evaluate the effect of the addition of natural sweeteners stevia and citric acid on color changes in butterfly pea flower syrup, which is rich in anthocyanin pigments. Anthocyanins give a distinctive blue color to telang flowers and are sensitive to changes in pH. The research method used a 3-factorial completely randomized design (CRD) with variations in the concentration of stevia leaf extract, stevia sugar, and the volume of lemon juice as a source of citric acid. The analysis included organoleptic test, anthocyanin qualitative test, total sugar test, viscosity test, and L*a*b* color test. The results showed that the addition of stevia leaf extract and citric acid significantly affected the color intensity of butterfly pea flower syrup. The combination of 30 grams of stevia leaf extract and 50 mL lemon juice produced the highest blue to violet color change based on the L*a*b* value. However, based on the organoleptic test, panelists preferred the sample with 10 grams of stevia leaf extract and 30 mL lemon juice. In the treatment with stevia sugar, the combination of 30 grams of stevia sugar and 30 mL of lemon juice produced the most preferred color.